Enhancing Children's Spiritual Language Expression Through the Picture Story Method in Islamic Early Childhood Education - Aziz, Mursal; Napitupulu, Dedi Sahputra; Baho, Rosvita Br (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Many young children are not yet accustomed to expressing Islamic values through verbal habits such as kalimat thayyibah (e.g., bismillah, alhamdulillah). This study explores the effectiveness of the picture story method in enhancing early childhood spiritual language expression. Using a Classroom Action Research (CAR) design, the study was conducted in two cycles at an Islamic kindergarten with 12 students. Data were collected through observation, interviews, and documentation. In Cycle 1, 75% of students met the learning criteria, which increased to 91.6% in Cycle 2. These findings indicate that integrating visual narratives with Islamic verbal expressions fosters the contextual use of kalimat thayyibah among young children. This method not only enhances language development but also supports character formation, offering valuable insights into spiritual pedagogy in early childhood Islamic education.